Objectively measured sleep characteristics and prevalence of coronary artery calcification: The Multi-Ethnic Study of Atherosclerosis Sleep Study - Lutsey, Pamela L (Thorax, 2015)
BACKGROUND: We tested whether objectively measured indices of obstructive sleep apnea (OSA) and sleep quality are associated with coronary artery calcification (CAC) prevalence independent of obesity, a classic confounder. METHODS: A total of 1,465 Multi-Ethnic Study of Atherosclerosis participants [mean age 68 years], who were free of clinical cardiovascular disease, had both coronary CT and in-home polysomnography and actigraphy. OSA categories were defined by apnea-hypopnea index (AHI). Prevalence ratios for CAC >0 and >400 (high burden) were calculated. RESULTS: Participants with severe OSA (AHI ≥ 30; 14.6%) were more likely to have prevalent CAC, relative to those with no evidence of OSA, after adjustment for demographics and smoking status [1.16 (95% CI: 1.06–1.26)], body mass index [1.11 (1.02–1.21)], and traditional cardiovascular risk factors [1.10 (1.01–1.19)]. Other markers of hypoxemia tended to be associated with higher prevalence of CAC >0. For CAC >400 a higher prevalence was observed with both a higher arousal index and less slow-wave sleep. Overall, associations were somewhat stronger among younger participants, but did not vary by sex or race/ethnicity. CONCLUSIONS: In this population-based multiethnic sample severe OSA was associated with subclinical coronary artery disease (CAC >0), independent of obesity and traditional cardiovascular risk factors. Furthermore, the associations of the arousal index and slow wave sleep with high CAC burden suggest that higher nightly sympathetic nervous system activation is also a risk factor. These findings highlight the potential importance in measuring disturbances in OSA as well as in sleep fragmentation as possible risk factors for coronary artery disease.